2017
DOI: 10.1111/jep.12807
|View full text |Cite
|
Sign up to set email alerts
|

Why “Animal (De)liberation” survives early criticism and is pivotal to public health

Abstract: SummaryIn 2016, the book Animal (De)liberation: Should the Consumption of Animal Products Be Banned? was published. This article aims to engage with the critique that this book has received and to clarify and reinforce its importance for human health. It is argued that the ideas developed in the book withstand critical scrutiny. As qualified moral veganism avoids the pitfalls of other moral positions on human diets, public health policies must be altered accordingly, subject to adequate political support for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…This section opens with a characteristically timely response on the part of Deckers 43 to the review that concluded our previous section. He accepts the criticism that he does not provide enough detail on what a qualified ban on the consumption of animal products might look like, a limitation he attributes to a number of factors, including "the complex business of evaluating the GHIs, for example the environmental costs and benefits of actual and potential diets."…”
Section: Debatesmentioning
confidence: 99%
See 3 more Smart Citations
“…This section opens with a characteristically timely response on the part of Deckers 43 to the review that concluded our previous section. He accepts the criticism that he does not provide enough detail on what a qualified ban on the consumption of animal products might look like, a limitation he attributes to a number of factors, including "the complex business of evaluating the GHIs, for example the environmental costs and benefits of actual and potential diets."…”
Section: Debatesmentioning
confidence: 99%
“…This section opens with a characteristically timely response on the part of Deckers to the review that concluded our previous section. He accepts the criticism that he does not provide enough detail on what a qualified ban on the consumption of animal products might look like, a limitation he attributes to a number of factors, including “the complex business of evaluating the GHIs, for example the environmental costs and benefits of actual and potential diets.” However, he states that as “more people take the key question addressed by the book seriously, it is my hope that further studies and value discussions will refine GHI calculations.” His article addresses several other criticisms levelled by Laestadius and other commentators, including his moral endorsement of a version of “speciesism” and the prioritization of human health—positions that might seem to place him at odds with many other advocates of veganism, most notably Singer .…”
Section: Debatesmentioning
confidence: 99%
See 2 more Smart Citations
“…Those who adopt this ontology may recognise more clearly that sentient beings must kill other sentient beings to sustain themselves. As I have argued in detail elsewhere, the question which sentient beings should be allowed to be killed should be settled not only by taking account of differences in sentient capacities, but also by the degree to which a being is related to a human being, an extension of speciesism that has been labelled as evolutionism (Deckers, 2017;Paez, 2017). Whilst this theory has been subjected to critical scrutiny by other scholars and has its own problems (Laestadius, 2017;Mancilla, 2016;Paez, 2017), it provides a superior account of animal ethics to that developed by Haynes.…”
Section: Discussionmentioning
confidence: 99%